Novel cannabidiol sunscreen protects keratinocytes and melanocytes against ultraviolet B radiation. (16th September 2020) - Gohad, Pranjal; McCoy, John; Wambier, Carlos; Kovacevic, Maja; Situm, Mirna; Stanimirovic, Andrija; Goren, Andy
Abstract: Cannabidiol (CBD), a natural occurring phytocannabinoid, is used extensively in consumer products ranging from foods to shampoos, topical oils and lotions. Several studies demonstrated the anti‐inflammatory and antioxidative properties of cannabidiol. Nevertheless, the role of cannabidiol use in sunscreens is largely unknown as no studies on its effect on keratinocytes or melanocytes exist. As such, we aimed to explore the effect of CBD on keratinocyte and melanocyte viability following ultraviolet B (UVB) irradiation. CBD exhibited a dose‐dependent protective effect on both keratinocytes and melanocyte viability. Further, since CBD does not demonstrate absorption in the UVB spectra, we speculate that the protective effect is due to reduction in reactive oxygen species. To our knowledge, this is the first study demonstrating the protective effect of CBD on keratinocytes and melanocytes irradiated with UVB.